Down to Earth: persons in place in natural history - Rolston, Holmes, 1932-2025, author; Roman and Littlefield Publishers, publisher (Colorado State University. Libraries, 1998)
On Earth living things have home territories. Biology, the logic of life, is always historical or "geographical," graphed out as world lines by embodied beings emplaced in Earth's natural history. Cultural history brings radical innovations. Modern humans do not live in niches in ecosystems; culture and agriculture, industry and technology transform those dependencies. Still, life remains storied residence on landscapes, where culture is, or ought to be, in harmony with nature. Humans can stand apart from the world and consider themselves in relation to it. An earth ethics ought to discover a global obligation to the whole inhabited planet.
Keywords: earth ethics; global ethics; agriculture; culture; ecosystem niches; natural history; geographical biology; historical biology; harmony with nature; humans part of nature; humans apart from nature